Genetic diversity among red mombin fruits in the Southwest of Goiás - Pereira , Laísse Danielle; Ferreira de Souza, Lasara Kamila; Dias do Valle, Karminne; Rodrigues Gomes, Francielly; Naves Pinto, Jefferson Fernando; Pereira da Silva, Danielle Fabíola (Revista Ceres, 2025)
The identification of productive plants with fruits of desirable characteristics contributes to the optimization of commercial crops of red mombin fruits. The aim of this work was to evaluate the genetic diversity among the provenance of red mombin of two municipalities of the state of Goiás. The fruits were harvested at ripening stage 3 and transported to the laboratory. The treatments were composed of fruits harvested from three plants, being ten repetitions and five fruits per experimental plot, totaling fifty fruits per provenance. Considering each repetition as an individual, 15 individuals were evaluated for length, diameter, weight, color attributes of the pericarp and pulp, soluble solids content and titratable acidity of the pulp, ratio of soluble solids content and acidity, and vitamin C content of the pulp. The results were subjected to descriptive analysis. A multivariate analysis was performed estimating the mean Euclidean distance obtained from the provenances, based on the attributes of the fruits analyzed. The measure of similarity and grouping of the provenances were done through the Tocher optimization algorithm and UPGMA dendrogram. The variables contributed similarly to dissimilarity. The Tocher method grouped the individuals into four groups, while in the UPGMA dendrogram, seven groups were formed.